Treatment of pruritus with botulinum toxin in a pediatric patient with Fox‐Fordyce disease. Issue 4 (1st June 2021) - Klager, Skylar; Kumar, Monique Gupta
Abstract: Fox‐Fordyce disease is a chronic pruritic disorder of apocrine sweat glands that is often associated with significantly decreased quality of life. With no definitive cure, affected patients are often treated with topical corticosteroids as first‐line therapy, but evidence for treatment of refractory cases is limited. We present an adolescent with Fox‐Fordyce disease successfully treated for symptomatic relief with botulinum toxin type A injections. While previously reported in an adult patient, we detail the efficacy of this therapy in a pediatric patient.